PENINGKATAN KETERAMPILAN BAHASA INDONESIA DENGAN MENUMBUHKAN MINAT MEMBACA SISWA KELAS V DI SDN 003 KECAMATAN RAMBAH - Yasnimar Yasnimar (STKIP ROKANIA, 2019)
This study aims to improve reading skills by fostering reading interest in fifth grade students at SDN 003 Rambah. This type of research is classroom action research. The results of the learning process before growing interest in reading reached an average value of 63.4%. After being motivated by interest in cycle I and cycle II, reflection and recommendations averaged 81.4%, meaning there was an increase of 18%. Learning outcomes before cycle I and cycle II reach an average value of 79.1%, after cycle I and cycle II, reflection and recommendations averaged 84.6%, meaning there was an increase of 5.5%. So growing interest in reading can improve Indonesian language skills in Grade V SDN 003 Rambah Rambah District, Rokan Hulu Regency.